Exploring English Professional Teacher Identity in An Islamic School - Nadiah Ma’mun; Januarius Mujiyanto; Rudi Hartono; Hendi Pratama (Universitas Negeri Semarang, 2022)
Many elements, including the teacher professional identity, have an impact on the educational quality, especially in the language teaching and learning process. A teacher's professional identity has a part in building how successfully they fulfil their position as a teacher. Students who will be guided toward having good knowledge and value will affect their success. Since teaching is a socially oriented profession, teacher professional identity affects not just instructors' expectations of what they should do to become good/professional teachers but also their students' identities. Teachers' preferences and expectations for the future growth of their students are influenced by their professional identities. This study attempts to explore how the teachers construct their professional identity in An Islamic School. A narrative case study methodology is employed in this investigation. The data are gathered from two participants of English teachers from one of Islamic Junior High School in Ngaliyan district, Semarang. The study showcases how the English teachers at Islamic School construct and negotiate their professional identity as a moral and character gate keepers.